2011
DOI: 10.5114/aoms.2011.22077
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blood pressure levels and bone mineral density in postmenopausal Turkish women

Abstract: IntroductionWe investigated the association between bone mineral density (BMD) detected by dual-energy X-ray absorptiometric (DXA) method and blood pressure (BP) in a large sample of postmenopausal women.Material and methodsThe current study was based on a retrospective analysis of 586 postmenopausal women with a mean age of 60.8 ±8.8 years, who were screened for osteopenia or osteoporosis by DXA. Patients with hypertension (HT, n= 306) were compared with normotensive (NT, n = 290) individuals. Bone mineral de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
1
21
2
1
Order By: Relevance
“…In fact, cross-sectional analyses and prospective studies revealed that 25-hydroxy vitamin D (25-OHD) serum levels were inversely related to high cardiovascular risk [35] and calcium metabolism and the cardiovascular system may have an interaction [6]. On the other hand, normalisation of 25-OHD level by exogenous supplementation is associated with a slight but significant improvement in blood pressure [710].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, cross-sectional analyses and prospective studies revealed that 25-hydroxy vitamin D (25-OHD) serum levels were inversely related to high cardiovascular risk [35] and calcium metabolism and the cardiovascular system may have an interaction [6]. On the other hand, normalisation of 25-OHD level by exogenous supplementation is associated with a slight but significant improvement in blood pressure [710].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is a serious health problem in our country, as in many other countries (1). In the diagnosis and followup of osteoporosis, double-energy X-ray absorptiometry (DXA) management is used as the golden standard (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis (OP) is characterized with a decrease in bone density and increasing bone fragility, spoiling the micro-structure of bone structure, and affects millions of women and men and is a frequently seen, chronic, progressive, and systemic disease (1)(2)(3). Osteoporosis is a serious health problem in our country, as in many other countries (1).…”
Section: Introductionmentioning
confidence: 99%
“…Although in this study there is no relationship was found between blood pressure and bone density, the direction of correlation is negative. Yazici et al (2011) mentioned that hypertension is a predictor of osteopenia and osteoporosis. Other studies suggest that bone mineral content (BMC) in juvenile hypertension is lower than the non-hypertensive teenagers (Pludowski et al 2007).…”
Section: Correlation Between Metabolic Syndrome Components Confoundimentioning
confidence: 99%